Cambridge International AS level and A Level physics teacher's resource [ - Sang (Cambridge: Cambridge University Press, 2010)
CD-ROM for Windows and Mac OSX
To accompany textbook titled "Cambridge AS level and A level physics coursebook / David Sang ... [et al.]"
SAM
Keywords: Physics